2005
DOI: 10.1016/j.socscimed.2005.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Health status among young people in Slovakia: comparisons on the basis of age, gender and education

Abstract: Health status among young people in Slovakia Sleskova, M.; Salonna, F.; Madarasova-Geckova, A.; van Dijk, J.P.; Groothoff, J.W. AbstractThis study examines the health status of young people in Slovakia. Six subjective health indicators (self-rated health, long-standing illness, vitality, mental health, long-term well-being over the last year and occurrence of health complaints during the previous month) were used to assess the health status of three age groups: first grade secondary school students (mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
1
10
0
6
Order By: Relevance
“…Five of these studies presented longitudinal survey data (Grimmer, Nyland, & Milanese, 2006; Laaksonen et al., 2010; Larsson & Sund, 2005; Palacio-Vieira et al., 2008; Sweeting & West, 2003), 26 (repeat) cross-sectional survey data (Bigal et al., 2007; Bisegger et al., 2005; Cavallo et al., 2006; Gadin & Hammarstrom, 2000; Gordon et al., 2004; Haugland et al., 2001; Heinrich, Morris, & Kroner-Herwig, 2009; Holmberg & Hellberg, 2007; Jorngarden, Wettergen, & von Essen, 2006; Kujala, Taimela, & Viljanen, 1999; Laurell, Larsson, & Eeg-Olofsson, 2004; Leonardsson-Hellgren, Gustavsson, & Lindblad, 2001; Lundqvist, Clench-Aas, Hofoss, & Bartonova, 2006; Mavromichalis, Anagnostopoulos, Metaxas, & Papanastassiou, 1999; Meland et al., 2007; Mortimer, Kay, & Jaron, 1992, 1993; Ostberg, Alfven, & Hjern, 2006; Petersen, Bergstrom, & Brulin, 2003; Ravens-Sieberer, Erhart, Wille, Bullinger, & Bella Study Group, 2008; Rhee et al., 2005; Santinello et al., 2009; Sleskova, Salonna, Madarasova Geckova, van Dijk, & Groothoff, 2005; Sundblad, Saartok, & Engstrom, 2007; Torsheim et al., 2006; Wedderkopp, Leboeuf-Yde, Andersen, Froberg, & Hansen, 2001), and 10 routinely collected data (Beilmann et al., 1999; Carle et al., 2004; Casu, Pascutto, Bernardinelli, Sardinian IDDM Epidemiology Study Group, & Songini, 2004; Christensen et al., 2007; Cinek et al., 2000; Cotellessa et al., 2003; Freitag, May, Pfafflin, Konig, & Rating, 2001; Karvonen et al., 1999; Michalkova, Cernay, Dankova, Rusnak, & Fandakova, 1995; Skordis et al., 2002), such as clinic/hospital statistics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of these studies presented longitudinal survey data (Grimmer, Nyland, & Milanese, 2006; Laaksonen et al., 2010; Larsson & Sund, 2005; Palacio-Vieira et al., 2008; Sweeting & West, 2003), 26 (repeat) cross-sectional survey data (Bigal et al., 2007; Bisegger et al., 2005; Cavallo et al., 2006; Gadin & Hammarstrom, 2000; Gordon et al., 2004; Haugland et al., 2001; Heinrich, Morris, & Kroner-Herwig, 2009; Holmberg & Hellberg, 2007; Jorngarden, Wettergen, & von Essen, 2006; Kujala, Taimela, & Viljanen, 1999; Laurell, Larsson, & Eeg-Olofsson, 2004; Leonardsson-Hellgren, Gustavsson, & Lindblad, 2001; Lundqvist, Clench-Aas, Hofoss, & Bartonova, 2006; Mavromichalis, Anagnostopoulos, Metaxas, & Papanastassiou, 1999; Meland et al., 2007; Mortimer, Kay, & Jaron, 1992, 1993; Ostberg, Alfven, & Hjern, 2006; Petersen, Bergstrom, & Brulin, 2003; Ravens-Sieberer, Erhart, Wille, Bullinger, & Bella Study Group, 2008; Rhee et al., 2005; Santinello et al., 2009; Sleskova, Salonna, Madarasova Geckova, van Dijk, & Groothoff, 2005; Sundblad, Saartok, & Engstrom, 2007; Torsheim et al., 2006; Wedderkopp, Leboeuf-Yde, Andersen, Froberg, & Hansen, 2001), and 10 routinely collected data (Beilmann et al., 1999; Carle et al., 2004; Casu, Pascutto, Bernardinelli, Sardinian IDDM Epidemiology Study Group, & Songini, 2004; Christensen et al., 2007; Cinek et al., 2000; Cotellessa et al., 2003; Freitag, May, Pfafflin, Konig, & Rating, 2001; Karvonen et al., 1999; Michalkova, Cernay, Dankova, Rusnak, & Fandakova, 1995; Skordis et al., 2002), such as clinic/hospital statistics.…”
Section: Resultsmentioning
confidence: 99%
“…These were a cross-sectional study (Cavallo et al., 2006) reporting an increasing female excess of fair/poor (vs. good/excellent) health between ages 11 (OR 1.36) and 15 (OR 1.97), and a longitudinal study (Sweeting & West, 2003) in which the female excess of fairly/not good (vs. good) health increased from OR of 1.01 at 11 to 1.44 at age 15. The other three cross-sectional studies of poor categorical self-assessed health shown on Table 2 (Holmberg & Hellberg, 2007; Meland et al., 2007; Sleskova et al., 2005) did not find statistically significant gender-by-age interactions, although the data presented by Holmberg and Hellberg (2007) suggest an increasing female excess.…”
Section: Resultsmentioning
confidence: 99%
“…The higher risk of mental disorders among girls has been found internationally in many investigations [25][26][27][28][29]. In a study in high school students in Kurdistan, in western Iran, 27% of boys and 46% of girls were aware that they had mental health problems [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our sample consisted of 1992 secondary school students from 24 secondary schools in the Kosice region in Slovakia (Sleskova, Salonna, Madarasova Geckova, van Dijk, & Groothoff, 2005). The Slovakian school system is as follows: After leaving elementary school (9 years attendance), Slovak adolescents aged around 15 enter one of four types of secondary schools: 1) a four-year grammar school providing general education and preparation for university study.…”
Section: Sample and Proceduresmentioning
confidence: 99%